Frequency estimation by iterative interpolation based on leakage compensation. (January 2015) - Diao, Ruipeng; Meng, Qingfeng
Highlights: An iterative interpolation estimation of parameters for multi-frequency is proposed. The proposed method can effectively eliminate short-range and long-range leakage. The convergence speed of the proposed algorithm is very fast. The estimated accuracy is higher than typical interpolation method. The proposed method suits for the instrument with poor computing resource. Abstract: An iterative interpolation method for estimation parameters that characterize a linear combination of sinusoids is presented. It is based on the analysis of the generation principle of the spectrum leakage, picket fence effect and an interpolation scheme applied to the discrete Fourier transform, and is described as follows: (1) Estimate parameters by traditional interpolation method; (2) obtain the leakage compensation factors; (3) re-calculate parameters by interpolation method based on leakage compensation; Repeat (2) and (3) until obtain the high precision result. The simulation results show that the proposed iterative method has the better estimation accuracy and stability under noise and the severe long-range leakage situation, and has fast convergence rate. It can be used as an alternative method to improve parameter estimation accuracy of the discrete Fourier transform.